Women are the mothers of the world - Abd Razak, Dzulkifli (2007)
LAST week was Mothers' Day. A perfect reminder that we owe much to this one person for bringing us into this world. Intrinsic to the understanding of the intricate biological process of giving birth is "menstruation". Menstruation can be an indication that pregnancy has not occurred. It is also commonly called "period" because of the periodic flow of blood and cells from the lining of the womb, once every 28 days or so. It lasts three to five days. Interestingly, besides humans, only the great apes exhibit such physiological cycles; what most mammalian species exhibit is called the estrus cycle. But to some, this vital biological process is crudely known as a "leak". Some even draw comparisons to a mechanical leak in the roof of a building. Such insinuations, in jest or otherwise, invariably leave a bad taste in the mouth. They are sexist and boils down to being disrespectful not only to women, but to a bodily function which is finely balanced to ensure the survival of the human species.